2017
DOI: 10.1016/j.envpol.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on heat-related mortality in Jiangsu Province, China

Abstract: A warming climate is anticipated to increase the future heat-related total mortality in urban areas. However, little evidence has been reported for cause-specific mortality or nonurban areas. Here we assessed the impact of climate change on heat-related total and cause-specific mortality in both urban and rural counties of Jiangsu Province, China in the next five decades. To address the potential uncertainty in projecting future heat-related mortality, we applied localized urban- and nonurban-specific exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 44 publications
3
58
0
Order By: Relevance
“…Statistical data have shown that the incidences of HS and HSinduced deaths are increasing each year. However, the existing data are limited to some cities or provinces with small sample sizes, and as a result, they have limited reference value [19][20][21][22]. Currently, large-scale HS epidemiology data are still lacking in China.…”
Section: Epidemiologymentioning
confidence: 99%
“…Statistical data have shown that the incidences of HS and HSinduced deaths are increasing each year. However, the existing data are limited to some cities or provinces with small sample sizes, and as a result, they have limited reference value [19][20][21][22]. Currently, large-scale HS epidemiology data are still lacking in China.…”
Section: Epidemiologymentioning
confidence: 99%
“…Thus, more studies should be extended to take account of the whole range of effects associated with ambient temperature. Some studies have been published concerning the impact of daily ambient temperature on mortality or morbidity [14,15]. However, those approaches failed to consider the differences in age, resulting in incomplete analysis of information.…”
Section: Of 12mentioning
confidence: 99%
“…The assumption for the population projection for Germany under different SSPs are medium fertility, low mortality, medium migration and high education for SSP1; medium fertility, medium mortality, medium migration and medium education for SSP2; low fertility, high mortality, low migration and low education for SSP3; low fertility, medium mortality, medium migration and polarised education for SSP4; and high fertility, low mortality, high migration and high education for SSP5 [37]. Location-specific population projections were calculated by taking the sum of the populations of each grid cell covering the area of the location, a method used previously [16]. Additionally, we corrected the obtained projected population for bias by extracting the population for the year 2010 from the NCAR dataset and comparing it with the population record of the same year from the German census authority [26] in order to find the locationspecific correction factor.…”
Section: Population Projectionsmentioning
confidence: 99%
“…There exists evidence that a warming climate would result in higher future heat-related mortality [11][12][13][14]. Several studies also show an increasing impact of climate change on heat-related cause-specific mortality burden, such as cardiovascular and respiratory causes [15,16]. Yet, with increasing temperatures and assuming no adaptation of the future population, cold-related mortality burden will decrease in the future [8,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%